Huobahuagen tablet improves renal function in diabetic kidney disease: a real-world retrospective cohort study - Tan, Ying; Li, Ruihan; Zhou, Peipei; Li, Nan; Xu, Weilong; Zhou, Xiqiao; Yan, Qianhua; Yu, Jiangyi (Frontiers in Endocrinology, 2023)
Objective: We aimed to explore the value of Huobahuagen tablet (HBT) in improving decreased renal function for patients with diabetic kidney disease (DKD) over time. Methods：This was a single-center, retrospective, real-world study on eligible 122 DKD patients who continued to use HBT+HKC therapy or HKC therapy without interruption or alteration in Jiangsu Province Hospital of Chinese Medicine from July 2016 to March 2022. The primary observation outcomes included estimated glomerular filtration rate (eGFR) at baseline and at 1-, 3-, 6-, 9-, and 12-month follow-up visits and changes in eGFR from baseline (ΔeGFR). PS (propensity score) and IPTW (Inverse Probability Treatment Weight) were used to control for confounders. Results：eGFR was significantly higher in the HBT + HKC group than in the HKC alone group at the 6-, 9-, and 12-month follow-up visits (p = 0.0448, 0.0002, and 0.0037, respectively), indicating the superiority of HBT + HKC over HBT alone. Furthermore, ΔeGFR of the HBT + HKC group was significantly higher than that of the HKC alone group at the 6- and 12-month follow-up visits (p = 0.0369 and 0.0267, respectively). In the DKD G4 patients, eGFR was higher in the HBT + HKC group at the 1-, 3-, 6-, 9-, and 12-month follow-up visits compared with baseline, with statistically significant differences at the 1-, 3-, and 6- month follow-up visits (p = 0.0256, 0.0069, and 0.0252, respectively). The fluctuations in ΔeGFR ranged from 2.54 ± 4.34 to 5.01 ± 5.55 mL/min/1.73 m². Change in the urinary albumin/creatinine ratio from baseline did not exhibit a significant difference between the two groups at any of the follow-up visits (p > 0.05 for all). Adverse event incidence was low in both the groups. Conclusion：The findings of this study based on real-world clinical practice indicate that HBT + HKC therapy exhibited better efficacy in improving and protecting renal function with a favorable safety profile than HKC therapy alone. However, further large-scale prospective randomized controlled trials are warranted to confirm these results.